2014
DOI: 10.3233/jbr-140063
|View full text |Cite
|
Sign up to set email alerts
|

CATT as a non-chemical pest and nematode control method in strawberry mother planting stock1

Abstract: Abstract. Until 2008 methyl bromide (MeBr) was used in The Netherlands for fumigation of strawberry runners, intended as mother planting stock, to make them free of contamination by strawberry tarsonemid mites (Phytonemus pallidus). As an alternative of MeBr fumigation a 48 h CATT method was developed and scaled up by Wageningen UR in cooperation with the plant propagating association Plantum. This results in an excellent disinfection and a mortality of 99.8% of the strawberry tarsonemid mite. This method prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
1
2
0
1
Order By: Relevance
“…The 99.9% reduction of P. pallidus in this study is comparable to the mortality rate reported in previous research (van Kruistum et al 2011, 2014, Verschoor et al 2015) when strawberry plants were treated at 35 °C, 50% CO 2 , 10% O 2 , and high relative humidity for 48 h. Phytonemus pallidus is well protected from most acaricides and predatory mites because it lives hidden in the leaves and crowns of strawberry plants (Easterbrook et al 2001, Fountain et al 2010); however, CATT is highly effective because the plant does not provide protection from heat, high CO 2 and low O 2 levels in the atmosphere. While heat increases respiration rate, restricted amount of O 2 available to P. pallidus causes its suffocation (Mitcham et al 2006).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The 99.9% reduction of P. pallidus in this study is comparable to the mortality rate reported in previous research (van Kruistum et al 2011, 2014, Verschoor et al 2015) when strawberry plants were treated at 35 °C, 50% CO 2 , 10% O 2 , and high relative humidity for 48 h. Phytonemus pallidus is well protected from most acaricides and predatory mites because it lives hidden in the leaves and crowns of strawberry plants (Easterbrook et al 2001, Fountain et al 2010); however, CATT is highly effective because the plant does not provide protection from heat, high CO 2 and low O 2 levels in the atmosphere. While heat increases respiration rate, restricted amount of O 2 available to P. pallidus causes its suffocation (Mitcham et al 2006).…”
Section: Discussionsupporting
confidence: 90%
“…The controller was operated with a computer program created using the Cscape PLC Software 9.90 (Horner APG, 2020). The program specified a temperature of 35 °C, a relative humidity (RH) of 92%, a CO 2 concentration of 50%, and an O 2 concentration of 10% (van Kruistum et al 2011, 2014, Verschoor et al 2015). A proportional–integral–derivative (PID) control loop mechanism was used to regulate temperature and atmospheric conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Het zal echter niet voor alle plaag-product combinaties tot een effectieve behandeling zonder kwaliteitsverlies kunnen leiden. CATT-behandelingen (Naar: Neven and Johnson, 2017, nog niet gepubliceerd (van Kruistum et al 2014, Verschoor et al 2015 *Combinatie CATTS met daarna gekoelde opslag (7 weken @ 0°C). ** De projectgroep die deze behandeling financierde heeft geheimhouding van het gebruikte zuurstofgehalte afgesproken 1.1.1.1 Effect van CA op afdoding ongewenste organismen Ongewenste organismen zoals insecten, mijten of nematoden blijken niet altijd met een lineaire respons te reageren op verschillende CA condities en hoge temperaturen.…”
Section: Wat Is De Effectiviteit ?unclassified